2021
DOI: 10.1155/2021/6689727
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium officinale Regulates Fatty Acid Metabolism to Ameliorate Liver Lipid Accumulation in NAFLD Mice

Abstract: Dendrobium officinale (DOF) is a traditional Chinese edible and officinal plant. Ultrafine DOF powder (DOFP) can regulate lipids and histopathology in the liver, but the underlying mechanisms of hepatic fatty acid (FA) metabolism, which is generally correlated with the development of nonalcoholic fatty liver disease (NAFLD), remain unclear. The purpose of the present study was to investigate whether DOFP treatment alters hepatic FA metabolism in NAFLD mice by using multidimensional mass spectrometry-based shot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…We analyzed the protein expression levels of CPT1 and ACOX1 to evaluate whether the LPE treatment increases fatty acid β-oxidation. Studies show that CPT1 and ACOX1 induce β-oxidation [ 30 , 31 ]. CPT1 and ACOX1 protein expression levels were not significantly changed in the LPE administration groups compared to the HFD group ( Figure 4 E,F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the protein expression levels of CPT1 and ACOX1 to evaluate whether the LPE treatment increases fatty acid β-oxidation. Studies show that CPT1 and ACOX1 induce β-oxidation [ 30 , 31 ]. CPT1 and ACOX1 protein expression levels were not significantly changed in the LPE administration groups compared to the HFD group ( Figure 4 E,F).…”
Section: Resultsmentioning
confidence: 99%
“…CPT1 is an enzyme that transports FFA into mitochondria for oxidation to produce acetyl-CoA, which is subsequently used to generate ATP via the tricarboxylic acid cycle and electron transport chain [ 30 ]. ACOX1, along with peroxidase, is an initiating enzyme in the β-oxidation system [ 31 ]. When we investigated the expressions of ACOX1 and CPT1 in liver tissue, we found that LPE treatment did not affect the expression of these proteins ( Figure 4 E,F).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous literature showed that the total polysaccharide content (47.96%, w/w) and monosaccharide contents (consisted of D-mannose, glucose, galactose, and arabinose at 42.2%, 12.3%, 0.4%, and 0.4%, w/w) were detected in DOFP [18]. e total flavonoid content (3.78 ± 0.48%) and the content of naringenin (0.3601 ± 0.014 mg/g) in DOFP were detected in a sodium hydroxide-aluminum sulfate method and high-performance liquid chromatograph (HPLC) system (1260, Agilent, Germany), respectively, as described in our previous report [19]. Modern pharmacological studies have shown that polysaccharides have anti-inflammatory, antioxidant, antitumor, and other pharmacological effects, enhance immunity, and regulate intestinal flora [24].…”
Section: Discussionmentioning
confidence: 76%
“…After ultrafine pulverization, the particle size of a drug can reach 1-10 μm as an ultrafine powder [17]. e powder has the advantages of convenient transportation and storage, excellent water solubility, low loss of functional components, high utilization rate, and beneficial dietary fiber [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that Dendrobium officinale ultrafine powder (DOFP) could improve the intestinal flora and increase the SCFA level in feces and serum, thereby activating the SCFA-GPCR43/41 pathway, improving endothelial function, and lowering BP in rats with MH, which provides new insights on the mechanism of Dendrobium officinale in the treatment of MH ( Li et al, 2021 ). Polysaccharides, as the main medicinal ingredient of Dendrobium officinale , have gained increased research interest recently ( Lei et al, 2019 ; Zhang et al, 2020 ; Lei et al, 2021 ). However, it is not clear whether Dendrobium officinale polysaccharide (DOPS) can also improve the intestinal flora and SCFAs and then activate the intestinal SCFA-GPCR43/41 pathway, which can improve vascular function and lower the BP.…”
Section: Introductionmentioning
confidence: 99%